2018
DOI: 10.1128/mbio.00910-18
|View full text |Cite
|
Sign up to set email alerts
|

Trichomonas vaginalis Macrophage Migration Inhibitory Factor Mediates Parasite Survival during Nutrient Stress

Abstract: Trichomonas vaginalis is responsible for the most prevalent non-viral sexually transmitted disease worldwide, and yet the mechanisms used by this parasite to establish and maintain infection are poorly understood. We previously identified a T. vaginalis homologue (TvMIF) of a human cytokine, human macrophage migration inhibitory factor (huMIF). TvMIF mimics huMIF’s role in increasing cell growth and inhibiting apoptosis in human host cells. To interrogate a role of TvMIF in parasite survival during infection, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Additionally, MIF has been reported to enhance Myzus percicae and Acyrthosiphon pisum feeding [ 26 ], so we suggested that the high abundance expression of MIF in female mites might be related to this stage need for feeding a large amount of food to acquire nutrients before oviposition [ 26 ]. Additionally, MIF appeared with a higher transcript expression in starved mites, suggesting that Pso MIF may be beneficial for enhancing P. ovis survival under malnourished conditions [ 23 , 27 ] or seeking host or initiating feeding behavior [ 28 ], and that this similar function of MIF could increase parasite survival under adverse nutrient stress condition has been confirmed in Trichomonas vaginalis [ 27 ]. Several studies reported that MIF was clearly detectable in excretory/secretory products of the parasite [ 25 , 29 ], and the MIF was secreted by the parasite into host tissue and blood during infection [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, MIF has been reported to enhance Myzus percicae and Acyrthosiphon pisum feeding [ 26 ], so we suggested that the high abundance expression of MIF in female mites might be related to this stage need for feeding a large amount of food to acquire nutrients before oviposition [ 26 ]. Additionally, MIF appeared with a higher transcript expression in starved mites, suggesting that Pso MIF may be beneficial for enhancing P. ovis survival under malnourished conditions [ 23 , 27 ] or seeking host or initiating feeding behavior [ 28 ], and that this similar function of MIF could increase parasite survival under adverse nutrient stress condition has been confirmed in Trichomonas vaginalis [ 27 ]. Several studies reported that MIF was clearly detectable in excretory/secretory products of the parasite [ 25 , 29 ], and the MIF was secreted by the parasite into host tissue and blood during infection [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of trichomonas vaginalis to prostate disease is still unclear, so the treatment of such patients cannot yield the best‐expected results. As a crucial index after Trichomonas vaginalis, TvMIF can accurately restore infection status and MIF with the exact mechanism, since TvMIF has been verified to play a crucial role in the promotion of prostate disease development (Chen et al, 2018). Therefore, it is imperative that clinical research fully understands and explore the influence of TvMIF on the prostate.…”
Section: Discussionmentioning
confidence: 99%
“…During nutrient deprivation, overexpressed T. vaginalis macrophage migration inhibitory factor (TvMIF) was detected, which is a human cytokine homolog that mimics the HuMIF (human macrophage migration inhibitory factor). It has been proposed that this overexpression of TvMIF can inhibit ROS production and prevent ROS-induced apoptosis [24,25]. Interestingly, reactive nitrogen intermediates (RNI) may be associated with establishing an infection.…”
Section: The Avengers: the Cells Of The Host Immune System And Cytoki...mentioning
confidence: 99%